MODELS OF DISTANCE EDUCATION OF CHILDREN WITH DISABILITIES IN RUSSIA - I. V. Suvorova (Russian State Vocational Pedagogical University, 2015)
The paper summaries the experience of implementing the information and communications technologies of distance learning recommended to children with disabilities; the need for distance learning of disabled children being denoted along with the concept of distance learning technologies. The author gives the general characteristics of existing informational educational platforms of the "Tele-school" and "I-school", functioning as the network resources and available in most regions of theRussian Federation. They give the necessary informational and methodological support to the distance education centers, organized for coordinating and guaranteeing the distance learning of children with disabilities; the main functions of the centers and the distance education models being outlined. The author considers the distance learning as a prospective educational trend supported by the state and society including teachers, parents and children. However, any educational model should comply with the unified requirements - i.e. availability of education, adaptability to different levels, needs and specifics of disabled children, and health protection.